2023
DOI: 10.3390/medicina59081423
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Surgical Management of Insulinomas—A 23-Year Single-Center Experience

Abstract: Background and Objectives: Insulinoma is a rare tumor of the Langerhans islets of the pancreas. It produces insulin and causes severe hypoglycemia with neuroglycopenic symptoms. The incidence is low, at about 1–2 per 1 million inhabitants per year. The diagnosis is based on the presence of Whipple’s triad and the result of a fasting test. Surgery is the treatment of choice. Objectives: A retrospective observational study of patients operated on for insulinoma in our hospital focused on the diagnosis, the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…A considerable number of patients diagnosed with F-PNETs, which frequently occur in conjunction with MEN1, commonly exhibit the presence of multiple small pancreatic lesions. Two-thirds of insulinomas are smaller than 2 cm and 30% are smaller than 1 cm ( 50 ). Numerous studies in the literature have demonstrated the superiority of EUS over CT and MRI in detecting small pancreatic lesions ( 27 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of patients diagnosed with F-PNETs, which frequently occur in conjunction with MEN1, commonly exhibit the presence of multiple small pancreatic lesions. Two-thirds of insulinomas are smaller than 2 cm and 30% are smaller than 1 cm ( 50 ). Numerous studies in the literature have demonstrated the superiority of EUS over CT and MRI in detecting small pancreatic lesions ( 27 , 47 ).…”
Section: Discussionmentioning
confidence: 99%